Determining areas of improvement in quranic arabic vocabulary learning mobile applications through analysis of app user reviews - Mustaffa, F. Y. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Muslims constitute roughly around one fifth of the world population, the majority of which are not Arabic speakers. This poses a problem for them in their devotional activities such as performing the five obligatory daily prayers and reading the Holy Qur’an because they could not understand what they are reciting or reading. Added to this, Muslim adults who are busy working usually find it hard to find the time to attend Quranic Arabic classes. In order to rectify this problem, some mobile app developers have created apps with the objective of teaching Muslims Quranic Arabic vocabulary items so that they could begin to learn and understand Quranic Arabic. In March 2019, there are about eleven Quranic Arabic vocabulary teaching mobile applications which could be downloaded from Google Play Store. These apps come with differing features and are of varying quality. This exploratory qualitative study aims to analyze the user reviews of these apps in order to determine areas where they can be further improved by the developers. The findings of this research found that generally developers should concentrate on three areas of improvement; their applications’ content, technical capability, and pricing strategy. It is hoped that the findings from this study can be used by Quranic Arabic vocabulary mobile app developers to further improve their apps so that the Muslim public can benefit more from them.